Analisis Faktor Risiko Hipertensi Di Wilayah Provinsi Lampung (Analisis Data Riskesdas 2018) - Diah Adelia Emilda; Achmad Farich; Agung Aji Perdana; Fitri Ekasari; Khoidar Amirus (Postgraduate, University of Mataram, 2023)
Hypertension is systolic blood pressure ≥ 140, and diastolic ≥ 90 mmHg (Unger et al., 2020). Indonesia showed an increase from the 2013 Riskesdas data (25.8%) and 2018 Riskesdas (34.11%). Lampung ranks 16th with the highest number of hypertension in Indonesia with a presentation reaching 29.94% (Kemenkes RI, 2019) and (Kementrian Kesehatan Republik Indonesia, 2018). This research aims to determine the risk factors for hypertension in the Lampung province community using 2018 Riskesdas data. Using secondary data with a quantitative research type and cross-sectional design. The research population was the total sample of the 2018 Riskesdas in Lampung Province, namely 22,345 individuals, and the sample excluding pregnant data and incomplete data resulted in a sample of 11,095 individuals. Data analysis used univariate, chi-square, and multiple logistic regression. Bivariate test results of gender, age, education, diabetes mellitus, salty consumption, smoking, physical activity, obesity p-value α<0.05 means there is a significant relationship between gender, age, education, diabetes mellitus, salty consumption, smoking, physical activity, obesity on the incidence of hypertension in Lampung Province. Obesity has a modifying effect on the relationship between age and the incidence of hypertension, in obese people aged ≥45 the risk of experiencing hypertension is 3,804 times higher than those aged <45 years after controlling for gender, education, history of diabetes mellitus, salt consumption, smoking, and physical activity.